Preliminary assessment of effect of disturbance on natural regeneration in gaps of different sizes - Maame Esi Hammond; Radek Pokorný (Journal of Forest Science, 2020)
The study focused on natural regeneration of European beech (Fagus sylvatica), Norway spruce (Picea abies) and European larch (Larix decidua) within very small and four times bigger size gaps following a disturbance at a mixed temperate forest in the Czech Republic. In spring 2013, experimental gap design starts, when 1 m2 circular sampling plots along transects were delineated within four selected naturally occurring canopy openings with size below 20 m2. In December 2013, these initial canopy openings were artificially enlarged by felling to 226 m2 for small and 904 m2 for big gaps. Regeneration was monitored in the next two consecutive growing seasons after disturbance. Light conditions were measured before and after disturbance. Results indicated that four times larger gaps increased twice levels of light conditions, and that diffuse light starts to equilibrate to direct light there. Large gaps were favouring larch regeneration. Beech regeneration was predominant, independently on gap size as the study area belongs naturally to Beech Forest Vegetation Zone, however, the decline of spruce regeneration was presumably linked to drought. Gap size explained variation of larch regeneration in gaps. Contrarily, gap size could not be associated with the prolific regeneration of beech and abysmal regeneration performances of spruce in gaps.